A study on the user acceptance of the e-Lodgement in SSM / Ida Reena Nazri - Nazri, Ida Reena (Faculty of Business and Management, 2010)
This paper identifies the factors that determine users’ acceptance of e- Lodgement services and its causal relationships using a theoretical model based on the Technology Acceptance Model. Data relating to the constructs were collected from 98 respondents in Malacca and subjected to Structural Equation Modeling analysis. The proposed model fits the data well. Results indicate that the important determinants of user acceptance of the e- Lodgement services are perceived usefulness , Perceived ease of use, external factors, and intention to use e- Lodgement services/system. Finally, implications and recommendations of these finding are discussed.